If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13y + 39 = 11y + 15 Reorder the terms: 39 + 13y = 11y + 15 Reorder the terms: 39 + 13y = 15 + 11y Solving 39 + 13y = 15 + 11y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11y' to each side of the equation. 39 + 13y + -11y = 15 + 11y + -11y Combine like terms: 13y + -11y = 2y 39 + 2y = 15 + 11y + -11y Combine like terms: 11y + -11y = 0 39 + 2y = 15 + 0 39 + 2y = 15 Add '-39' to each side of the equation. 39 + -39 + 2y = 15 + -39 Combine like terms: 39 + -39 = 0 0 + 2y = 15 + -39 2y = 15 + -39 Combine like terms: 15 + -39 = -24 2y = -24 Divide each side by '2'. y = -12 Simplifying y = -12
| x^2+x(1-6q+q^2)+(-4q^3+8q^2-4q)=0 | | -5(2t-4)+6t=3t-5 | | 12-12x=23x | | y=4-3x+3 | | -4x^4(8-8x+3x^4)=0 | | 3(4z-8)-2= | | 10.50a+82=2017.50 | | 27=-9x-3y | | 14+0.1(x-300)=32.80 | | 3a-3b+3c=0 | | 5a+3b+2c=3a-3b+3c | | -3(4t-2)+5t=4t-4 | | 3a-3b+3b=0 | | z^2-2y+7z^2-2y+6z^2-22z^3+2-16y+2z^3= | | 5a+3b+2c=3a-3b+3b | | 9x-1=9(x-3) | | 5a+3b+2c=3a | | 14-7+12-18= | | 14ab-7ab+12b-18a+bc= | | 7x^4-14x^4+3x^3= | | 86-(3x+16)=3(x+7)+x | | 2(2m-2)-21= | | y=-1.04x+50.3 | | -3(0)+6y=-18 | | -3(5t-5)+7t=2t-6 | | 0=x^2-20x-224 | | 6x+3=6(x+8) | | -6(0)-6y=36 | | 2y^2-3y+9=0 | | 2x+7=2x-2.5 | | -6x-6(0)=36 | | 10-(3z-5)=1-4z |